Evaluating the timing of laparoscopic cholecystectomy for acute cholecystitis in an experienced center based on propensity score matching. Issue 2 (26th January 2017) - Asai, Koji; Watanabe, Manabu; Kusachi, Shinya; Matsukiyo, Hiroshi; Saito, Tomoaki; Ishii, Tomotaka; Kujiraoka, Manabu; Katagiri, Miwa; Katada, Natsuya; Saida, Yoshihisa
Abstract: Introduction: This study evaluates the therapeutic outcomes for laparoscopic cholecystectomy for acute cholecystitis based on the time from symptom onset to surgery. Methods: This study enrolled 224 patients. Patients' characteristics and operative outcomes were compared between patient groups based on the timing of laparoscopic cholecystectomy from symptom onset: ≤72 h versus >72 h, and ≤7 days versus ≥8 days. Then, we performed propensity score matching of 13 relevant variables, including patient demographics, examination findings, and therapeutic factors. Results: The early surgery groups (≤72 h and ≤7 days) had significantly younger patients with fewer comorbidities and a shorter duration from symptom onset to presentation before performed propensity score matching. These groups also had shorter surgery, postoperative hospital stay, and total length of stay. Other operative outcomes, including blood loss, conversion to open surgery, bile duct injury, and postoperative complications, did not significantly differ among the groups. After propensity score matching, all therapeutic outcomes, including duration of surgery, showed no significant differences in either analysis. Conclusions: In a center with sufficient experience, performing laparoscopic cholecystectomy at the earliest possible time after presentation was a safe therapeutic strategy for each patient with acute cholecystitis, regardless of the time from symptom onset.